Adverse Childhood Experiences in the Lives of Male Sex Offenders: Implications for Trauma-Informed Care. (June 2016) - Levenson, Jill S.; Willis, Gwenda M.; Prescott, David S.
This study explored the prevalence of childhood trauma in a sample of male sexual offenders ( N = 679) using the Adverse Childhood Experience (ACE) scale. Compared with males in the general population, sex offenders had more than 3 times the odds of child sexual abuse (CSA), nearly twice the odds of physical abuse, 13 times the odds of verbal abuse, and more than 4 times the odds of emotional neglect and coming from a broken home. Less than 16% endorsed zero ACEs and nearly half endorsed four or more. Multiple maltreatments often co-occurred with other types of household dysfunction, suggesting that many sex offenders were raised within a disordered social environment. Higher ACE scores were associated with higher risk scores. By enhancing our understanding of the frequency and correlates of early adverse experiences, we can better devise trauma-informed interventions that respond to the clinical needs of sex offender clients.